The microlearning – from business to education: A promising direction for the development of didactics - V. I. Blinov; I. S. Sergeev; N. F. Rodichev (Образование и наука)
Introduction. Microlearning is one of the modern trends in education, providing high motivation and involvement of students, fast and solid assimilation of the specified educational results, the connection of theory and practice, accessibility and flexibility of learning. At the same time, microlearning also has a number of serious drawbacks, primarily related to its content limitations, fragmentation and unsystematic nature, which prevents its widespread use at various levels of education. According to the authors of the article, these shortcomings are due to the peculiarities of a specific organisational and didactic model of microlearning used in corporate education. Attempts to directly transfer this approach to the system of general, secondary vocational, higher education are unproductive. The authors believe that it is necessary to develop a different didactic model of microlearning, adequate to the goals and approaches of the education system. The article presents a range of issues that are subject to priority resolution for the development of the theory of education, didactics and methodology in the context of the idea of microlearning. Aim. The present research aims to present a scientific approach to assess the possibilities of adapting the accumulated experience of using microlearning in mass educational practice.Methodology and research methods. The current research is based on methodological approaches of foreign and Russian scientists to the problems of digital transformation of education, primarily based on the idea of counter transformation of the educational process and digital tools, cultivation of systematic didactic knowledge. The leading method is the generalisation of scientific provisions, the analysis of practical experience and the creation of prerequisites for the creation of new knowledge.Results and scientific novelty. As a result of the research, the key directions of pedagogical scientific research are identified, ensuring continuity in the development of microlearning during its transfer from corporate education to use in mass educational practice. The novelty of the research is determined by the high demand for the development of didactic tools for organising the educational process, selecting and structuring the content of education.Practical significance. The research results can be applied in the process of training teachers for the broad implementation of microlearning during the digital transformation of education, as well as directly in the design of new digital tools.